A conspiracy of truths - Rowland, Alexandra (SAGA, an imprint of Simon & Schuster, Inc., 2018)
Arrested on accusations of witchcraft and treason, Chant finds himself trapped in a cold, filthy jail cell in a foreign land. With only his advocate, the unhelpful and uninterested Consanza, he quickly finds himself cast as a bargaining chip in a brewing battle between the five rulers of this small, backwards, and petty nation. Or, at least, that's how he would tell the story. In truth, Chant has little idea of what is happening outside the walls of his cell, but he must quickly start to unravel the puzzle of his imprisonment before they execute him for his alleged crimes. But Chant is no witch<U+2014>he is a member of a rare and obscure order of wandering storytellers. With no country to call his home, and no people to claim as his own, all Chant has is his wits and his apprentice, a lad more interested in wooing handsome shepherds than learning the ways of the world. And yet, he has one great power: his stories in the ears of the rulers determined to prosecute him for betraying a nation he knows next to nothing about. The tales he tells will topple the Queens of Nuryevet and just maybe, save his life.